1997
DOI: 10.1254/jjp.75.283
|View full text |Cite
|
Sign up to set email alerts
|

Chronotoxicity of Methotrexate in Mice and Its Relation to Circadian Rhythm of DNA Synthesis and Pharmacokinetics

Abstract: ABSTRACT-The mechanisms underlying the circadian rhythm of methotrexate (MTX)-induced toxicity (body weight loss and leukopenia) were investigated from the viewpoints of the sensitivity of living organ isms to the drug and the pharmacokinetics of the drug. ICR male mice were housed in a standardized light-dark cycle (lights on at 0700, off at 1900) with food and water ad libitum. The body weight loss after an intraperitoneal injection of MTX (400 mg/kg) was more serious in the late dark period and the early li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
1
18
2
Order By: Relevance
“…In previous studies, these doses of methotrexate alone disrupted conditioned taste aversion, conditioned emotional responses, spatial memory, and novel object recognition (Madhyastha et al 2002;Seigers et al 2008;Yanovski et al 1989) but failed to alter responding in a different conditioned taste aversion assay and a Pavlovian appetitive conditioning assay (Stock et al 1995). The doses of 3.2-32 mg/kg methotrexate used in mice and rats fall within the predicted 8-42-mg/kg-scaled mouse doses as determined from the range of clinical doses used to treat breast cancer in humans (40 mg/m 2 ) according to pharmacokinetic studies (Lobo and Balthasar 2003;Ohdo et al 1997;Peters et al 1993). When 75 mg/kg 5-fluorouracil was administered prior to the day 1 session, it failed to alter response rates or acquisition latency on day 1.…”
Section: Discussionmentioning
confidence: 98%
“…In previous studies, these doses of methotrexate alone disrupted conditioned taste aversion, conditioned emotional responses, spatial memory, and novel object recognition (Madhyastha et al 2002;Seigers et al 2008;Yanovski et al 1989) but failed to alter responding in a different conditioned taste aversion assay and a Pavlovian appetitive conditioning assay (Stock et al 1995). The doses of 3.2-32 mg/kg methotrexate used in mice and rats fall within the predicted 8-42-mg/kg-scaled mouse doses as determined from the range of clinical doses used to treat breast cancer in humans (40 mg/m 2 ) according to pharmacokinetic studies (Lobo and Balthasar 2003;Ohdo et al 1997;Peters et al 1993). When 75 mg/kg 5-fluorouracil was administered prior to the day 1 session, it failed to alter response rates or acquisition latency on day 1.…”
Section: Discussionmentioning
confidence: 98%
“…In mouse bone marrow cells, approximately 70-80% of the cells are in the G1 phase with 10-20% each in the S and G2/M phases. Circadian variations have been found for each cell cycle phase with G1 cells increasing in the dark period, and S and G2/M cells increasing in the light period (Granda et al, 2005;Ohdo et al, 1997). Therefore, the cell cycle may influence the different micronuclei appearances by chemicals between light and dark dosing times.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that chronochemotherapy can significantly prolong the overall survival of cancer patients when compared with conventional chemotherapy and its toxicity can be controlled[23]. Recently, the best times of administration of about 30 drugs have been found, including 5-fluorouracil, methotrexate, vinorelbine, etc [24], . However, the study on chronopharmacology of molecular targeted drugs has not been reported.…”
Section: Discussionmentioning
confidence: 99%